JFK's forgotten crisis : Tibet, the CIA, and Sino-Indian War - Riedel, Bruce (India Harper Collins Publishers, 2016)
This books explains about the crisis forgotten by John Fitzgerald Kennedy.
Include Acknowledgments, Chronology, Notes, Bibliography, Index and about the author.
It is about John Fitzgerald Kennedy's omitted crisis.
Keywords: Sino-Indian Border Dispute (1957-) -- United States -- Diplomatic relations -- India